Advanced Exergoeconomic Analysis of a Power Plant with CO2 Capture. (August 2015) - Petrakopoulou, Fontina; Tsatsaronis, George; Morosuk, Tatiana
Abstract: Conventional exergy-based analyses reveal options for improving energy conversion systems, but they suffer from some limitations that are addressed by advanced exergy-based analyses. Advanced exergy-based methods are capable of (1) identifying interdependencies among plant components (endogenous/exogenous values), and (2) revealing the potential for improvement (avoidable/unavoidable values). Thus, data obtained from these methods pinpoint strengths and weaknesses of energy conversion systems and are of great importance when complex plants with a large number of interconnected components are considered. This paper presents one of the first applications of an advanced exergoeconomic analysis to a complex power plant. The plant includes a mixed conducting membrane for oxy-fuel combustion and CO2 capture. The results show that for the most influential components of the plant, the largest part of investment cost and of the costs of exergy destruction is unavoidable. Additionally, in most cases the interactions among the components are of lower importance and, for the majority of the components, the endogenous parts of the costs (related to the internal operation of each component) are significantly larger than the corresponding exogenous parts (related to component interactions). Nevertheless, relatively strong interactions have been found among the components that constitute the mixed conducting membrane reactor of the plant.